The impact of a cancer diagnosis on sibling relationships from childhood through young adulthood: a systematic review. Issue 4 (7th August 2020) - Cheung, Christabel K.; Acquati, Chiara; Smith, Everett; Katerere-Virima, Thuli; Helbling, Laura; Betz, Gail
ABSTRACT: Cancer is a serious, life-threatening illness that impacts the entire family system, with implications for patients themselves, their siblings, parents, and extended family. Given increasing identification of siblings as uniquely important and enduring fixtures in each other's lives, investigation into the influence of cancer on sibling relationships is warranted. The current systematic review pursued the question: What interpersonal factors in sibling relationships are affected by coping with a cancer diagnosis from childhood through young adulthood? In September 2019, a systematic search of extant literature was conducted, from inception to present, resulting in nine studies meeting inclusion criteria. Results were sorted into psychosocial factors and family factors. Psychosocial factors included the quality of sibling relationships, social support, and psychological distress. Family factors included family functioning and family conflict. Findings suggest practice recommendations for peer support of siblings of cancer patients, as well as systemic and family-oriented interventions that harness strengths and prevent long-term negative effects on the entire family. Future research should expand knowledge on sibling relationships in the cancer context by examining their influence on practical issues such as financial burden, including a greater diversity of socio-demographic variables, and evaluating promising evidence-based models of care for oncology social work.